Проблемні питання законодавчого і прикладного удосконалення початкового етапу досудового розслідування - Юхно, О. О.; Yukhno, O. O.; Олександр Юхно (Вісник Київського національного університету імені Тараса Шевченка. Юридичні науки. – 2019. – Вип. № 1 (108). – С. 47-53, 2019)
Здійснено порівняльний аналіз попереднього і чинного кримінального процесуального законодавства України стосовно процесуального інституту початку досудового розслідування. Встановлені певні прогалини і неузгодженості в чинному КПК України, що викликає нарікання від учасників кримінального провадження у правозастосовній діяльності, а також дискусію серед учених і практиків із цих питань. Надано пропозиції з удосконалення чинного законодавства стосовно порушених проблем.

The author of the article conducts a comparative analysis of the previous and existing criminal procedural legislation of Ukraine regarding the procedural institution of starting criminal proceedings. Certain gaps and inconsistencies in the current criminal procedural legislation of Ukraine on these issues which cause justifiable complaints from all participants in the criminal proceedings are identified. The author analyses genesis, individual scientific points of view and the state of discussion among scientists and practitioners in this direction, as a result of which it is established that the problematic issues raised in the article are not resolved theoretically and in an applied aspect, including the previous and in the current criminal procedural legislation of Ukraine. In the context of the issue under consideration, the legislation of foreign countries is examined including post-Soviet states, Anglo-American and Roman-German legal families. As a result, many Ukrainian scientists have concluded that the foreign experience cannot be applied in national legislation without taking into account the national peculiarities of the legal system of Ukraine, the historical traditions of state construction, the level of professionalism and legal awareness of those who apply legislation, the mentality of the population and other factors. Moreover, the author pays paid attention to the study of discussion questions on the grounds and reasons for resolving the procedural problem of issuing a resolution when instituting criminal proceedings and when making statements and reports on committed criminal offenses in to the single register of pre-trial investigations, as well as refusing to register on these issues. The author makes some suggestions for improving the existing criminal procedural legislation and the regulatory framework in the context of the issues discussed.

Осуществлен сравнительный анализ предыдущего и действующего уголовного процессуального законодательства Украины относительно процессуального института начала досудебного расследования. Установлены определенные пробелы и несогласованности в действующем УПК Украины, что вызывает нарекания от участников уголовного производства в правоприменительной деятельности, а также дискуссию среди ученых и практиков по этим вопросам. Даны предложения по совершенствованию действующего законодательства относительно затронутых проблем.
Some problematic issues of legislative and applied improvement of the initial stage of pre-trial investigation
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; початок розслідування; кримінальне провадження; повідомлення; слідчий; прокурор; розкриття; регламентація; начало расследования; уголовное производство; следователь; раскрытие; регламентация; beginning of the investigation; criminal proceedings; improvement; notice; investigator; prosecutor; disclosure; regulation